Cribriform carcinoma in the lymph nodes is associated with distant metastasis, recurrence, and survival among patients with node-positive colorectal cancer. Issue 3 (11th January 2021) - Yokoyama, S; Fujita, Y; Matsumura, S; Yoshimura, T; Kinoshita, I; Watanabe, T; Tabata, H; Tsuji, T; Ozawa, S; Tamaki, T; Nakatani, Y; Oka, M
Abstract : Cribriform lymph node pattern is an independent risk factor for metachronous or synchronous distant metastasis in patients with stage III and IV node-positive colorectal cancer. Multivariable analysis in patients with stage III disease indicated that the cribriform pattern of carcinoma in the lymph nodes was an independent risk factor for recurrence and survival. Kaplan–Meier analysis demonstrated that the group with stage III cribriform-type lymph node carcinoma had shorter recurrence-free and overall survival times than the stage III group with the tubular type ( P < 0.001).